1999
DOI: 10.1002/(sici)1097-4652(199908)180:2<190::aid-jcp7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of selective cholesteryl ester uptake pathway in mice with deletion of low-density lipoprotein receptor function

Abstract: This study examines the effect of mutation of the low-density lipoprotein receptor (LDLR) on cholesterol metabolism, and especially lipoprotein-derived cholesteryl ester uptake, in murine ovarian granulosa cells. Although the tests were conducted on cells prepared by two different procedures, the results are similar. Deletion of LDLR function did not noticeably affect key enzymes of the steroidogenic pathway or affect progestin production and secretion in granulosa cells. No change was found in expression of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 70 publications
(83 reference statements)
1
13
1
Order By: Relevance
“…Surprisingly, treatment of rat ovarian granulosa cells with dibutyryl cAMP or folliclestimulating hormone down-regulated caveolin-1, though both SR-BI and selective uptake of CE were strongly induced (25). Caveolin-1 expression was not stimulated by similar hormone treatment of murine ovarian granulosa cells, although SR-BI expression and CE selective uptake were both induced (26). Similarly, in preliminary experiments, we found that though adrenocorticotropin hormone treatment of Y1 mouse adrenocortical cells stimulated SR-BI expression and CE selective uptake, caveolin-1 expression was not induced and may even have been reduced (M. A. Connelly and D. L. Williams, unpublished observations).…”
supporting
confidence: 58%
“…Surprisingly, treatment of rat ovarian granulosa cells with dibutyryl cAMP or folliclestimulating hormone down-regulated caveolin-1, though both SR-BI and selective uptake of CE were strongly induced (25). Caveolin-1 expression was not stimulated by similar hormone treatment of murine ovarian granulosa cells, although SR-BI expression and CE selective uptake were both induced (26). Similarly, in preliminary experiments, we found that though adrenocorticotropin hormone treatment of Y1 mouse adrenocortical cells stimulated SR-BI expression and CE selective uptake, caveolin-1 expression was not induced and may even have been reduced (M. A. Connelly and D. L. Williams, unpublished observations).…”
supporting
confidence: 58%
“…SR-B1 (or the high-density lipoprotein receptor) is thought to be a dominant pathway for cellular CE uptake. [12][13][14][15][16][17] It can also impact FC levels, potentially via a direct action 40,41 and/or by inhibiting the ABCA1 efflux pathway. 12 Given that CE overload was the dominant cholesterol change observed in these experiments, we hypothesized that this would induce a compensatory decrease in SR-B1 expression, because cells might attempt to limit the CE overload by specifically decreasing CE uptake.…”
Section: Discussionmentioning
confidence: 99%
“…8 -10 Secondly, increased filtration of FC-and CE-bearing lipoproteins might increase tubular cell cholesterol uptake, eg, via the high-density lipoprotein scavenger receptor-B1 (SR-B1) receptor. [11][12][13][14][15][16][17] The latter is particularly relevant for rats, given that high-density lipoprotein, rather than low-density lipoprotein, is the primary cholesterol carrier. 11 An alternative scenario might be that once cholesterol accumulation within glomerular and/or tubular cells is initiated, secondary compensatory mechanisms come into play that act to hold further cholesterol accumulation in check.…”
mentioning
confidence: 99%
“…Antibody-treated cells were subjected to standard immunochemical-labeling techniques (6,14,15,17,18) and viewed by confocal microscopy (Stanford University Cell Science Imaging Facility), and the resulting images were subsequently colorized by using PHOTOSHOP technology (Adobe Systems, Mountain View, CA).…”
Section: Sr-bi Expression Vectormentioning
confidence: 99%
“…For uptake and internalization studies, hHDL 3 preparations were conjugated with residualizing labels, i.e., (6,7,21). For fluorescence microscopy, reconstituted BODIPY-CE-HDL particles were prepared as described (9,14,15,17,18). ]COE-hHDL 3 (33 g͞ml medium) in the presence or absence of excess unlabeled hHDL 3 500 g͞ml medium, to determine nonspecific binding (6,11,21).…”
Section: Sr-bi Expression Vectormentioning
confidence: 99%